Accelerated success through leadership: a narrative study of female aviation executives’ stories of leadership development - Dreiling, Lindsey Rai (Kansas State University, 2023)
Women have a long history of involvement in aviation, yet they remain significantly underrepresented in the industry, particularly in senior leadership roles. Moreover, the limited number of women in the aviation pipeline, as seen in the low percentages of female FAA certificate holders, suggests that immediate progress in senior leadership numbers is unlikely. This study explores the experiences and perspectives of female aviation executives, aiming to shed light on their leadership development journeys. It considers factors contributing to their career advancement, the practices shaping the aviation industry's leadership landscape, and recommendations for effective leadership programs. Using an arts-based narrative approach, semi-structured interviews, and photovoice, this research uncovers ten key themes that emerged from the narratives of these executives. The findings emphasize the dynamic nature of leadership development, encompassing personal actions, industry practices, and structured training opportunities. Female aviation executives actively pursue self-improvement, embrace challenges, and engage in daily leadership interactions. Formal training initiatives play a pivotal role in enhancing these ongoing development efforts. This study presents a flight journey narrative structure, mirroring the executives' experiences in three legs, each representing a distinct aspect of leadership development. The model of aviation leadership development derived from the findings provides a comprehensive view of the practices at each leg of the journey. Addressing the gender gap in aviation leadership is not only a matter of equity but also has far-reaching implications for industry performance and meeting workforce needs. This research offers valuable insights for aviation companies, educational institutions, trade organizations, and government agencies seeking to support women's advancement in aviation and harness the industry's untapped potential. By fostering an inclusive culture and implementing intentional leadership programs, the aviation industry can fully engage the talent and perspectives that women bring, benefiting both individuals and the entire industry.
Keywords: Leadership development; Women executives; Aviation industry; Narrative inquiry; Photovoice; Female leadership